Analisis Potensi Pengembangan Ekmowisata Butta Gowa Resort Menjadi Destinasi Wisata Halal - Besse Faradiba (Jayapangus Press, 2023)
This study aims to analyze the potential for developing Ecotourism Butta Gowa Resort to become a halal tourist destination based on tourist perceptions and to evaluate strategic planning in developing halal tourism. The background of this research is because of the many facilities provided in the form of playgrounds to prayer facilities for Muslims by the Butta Gowa Resort ecotourism which is located on Jalan Malino Gowa, South Sulawesi Province, the Butta Gowa Resort Ecotourism is pressured to become one of the halal tourist destinations to attract the Muslim tourist market. This research method uses a mixed method where for quantitative it uses multiple linear regression with convenience sampling or purposive sampling where the proportional quota is 53 respondents and qualitatively uses SWOT analysis to evaluate strategies in developing halal tourism. The results show that the Global Muslim Travel Index criteria have an influence on tourist perceptions based on a quantitative descriptive approach where environmental variables have the greatest influence on tourist perceptions, followed by communication variables, then service variables and access variables so that Ecotourism Butta Gowa Resort has the potential to become a halal tourist destination then from the qualitative results it was found that the condition of the position of Ecotourism Butta Gowa Resort based on the results of calculating the scores and weights of various internal and external factors is in quadrant I of the SWOT matrix so that the right strategy is the S-O strategy where this strategy supports aggressive strategic policies when utilizing strengths and opportunities maximally. Further research is needed to find out other factors that can influence the perceptions of tourists visiting Butta Gowa Ecotourism.